Analisis Yuridis Kepastian Hukum Pajak dalam Transaksi Trading Forex dan Komoditi di Indonesia - Amin, Munafri; Ardiansyah, Ardiansyah (PT Elaborium Elevasi Indonesia, 2025)
Forex trading, as is known, is an effort made to predict prices from time to time, with the aim of making a profit. Although in reality the prediction is not always correct because of many influencing factors as explained in the previous paragraph. Technological advances greatly influence the development of this investment where we can easily enter the money market just by using a cellphone or laptop. The formulation of the problem is 1) How is the implementation of the Indonesian taxation system in supervising and enforcing tax compliance in forex transactions? 2) How do the tax regulations in Indonesia provide legal certainty regarding tax on forex transactions? The results of the study are that the implementation of the Indonesian taxation system in supervising and enforcing tax compliance in forex transactions (foreign exchange) is very important, considering the large transaction volume and the potential for state revenue that can be obtained from this sector. And the tax regulations in force in Indonesia affect tax compliance by forex traders through various channels, such as income reporting obligations, tax rate determination, sanctions applied, and supervision of forex transactions.